Esclerose Lateral Amiotrófica e as diversidades das distribuições das variantes (SNPs, indel) das enzimas de cadeia respiratória relacionadas à neuroproteção/neurodegeneração nas populações dos haplogrupos mitocondriais: uma análise de 1000 GENOME PROJECT - Mehrpour, Sheida [UNIFESP] (2019)
Amyotrophic Lateral Sclerosis (ALS) is a disease characterized by the degeneration of motor neurons in the brain and spinal cord, causing progressive, irreversible and incapacitating motor paralysis. Regarding the etiology of ALS, several factors have been included: acquired nuclear enzyme abnormalities, glutamate toxicity, oxidative stress, defective axonal transport, neurofilament abnormalities, genetic factors, viral infections, and mitochondrial dysfunction. There is strong evidence that mitochondria are one of the main targets of impairment in motor neurons, with changes in the electron transport complexes of the mitochondrial chain, affecting the final production of ATP. The impaired function of mitochondrial respiratory complexes has been linked to the quantitative and / or qualitative defects of these components. Previous studies have shown that some of the mitochondrial respiratory chain enzymes, including Riboflavin kinase (RFK), flavin adenine dinucleotide synthetase (FAD), Succinate dehydrogenase B subunit (SDHB), and Cytochrome C1 (CYC1) are associated with several mechanisms of neuroprotection and dysfunctions of these enzymes are related to neurodegeneration. In addition, there is evidence that these enzymes having quanitative defects are compromised in ALS patients. Considering that several studies have demonstrated an intimate relationship between mitochondria and ALS, we have proposed to rigorously analyze the information collected at the ENSEMBLE GENOME BROWSER 91 website (updated site of 1000 GENOME PROJECT, updated in December 2017), with variant description of the genes of these enzymes including RFK, FAD, SDHB, and CYC1, of the 2.540 individuals from 26 different populations of the five places of the world belong to the different mitochondrial haplogroups, identifying the distributions of the variants of these enzymes in the different populations of the mitochondria haplogroups. The study is based on the Hardy-Weinberg equilibrium calculation. Deviation of the Hardy-Weinberg equilibrium in the control group may reflect an expectation about the development of a disease or a clinical disorder or susceptibility to a disease. We were able to identify the diversity of the distributions of the mitochondrial respiratory chain enzymes variants including RFK, FAD, SDHB, and CYC1 in mitochondrial haplogroup populations by deviation of the equilibrium of certain variants of these enzymes, confirming the susceptibility of different haplogroup populations about ALS disease and through this information we can apply prognostic, diagnostic and therapeutic antioxidant strategies for ALS patients. This finding reflects how we conduct clinical trials in the individualized therapeutic determination of each ALS patient depending on the patient haologroup and the compromised enzyme.